Safety and efficacy of lecanemab for Alzheimer's disease: a systematic review and meta-analysis of randomized clinical trials - Qiao, Yue; Chi, Yuewei; Zhang, Qingyuan; Ma, Ying (Frontiers in Aging Neuroscience, 2023)
Objective We performed a systematic review and meta-analysis of the cognitive effectiveness and safety of lecanemab on subjects with Alzheimer's disease (AD). Methods We screened the literature published before February 2023 in PubMed, Embase, Web of Science, and Cochrane that were searched for randomized controlled trials testing lecanemab for the treatment of cognitive decline in patients with MCI or AD. Outcomes measured were CDR Sum of Boxes (CDR-SB), Alzheimer's Disease Composite Score (ADCOMS), AD Assessment Scale–Cognitive Subscale (ADAS-Cog), Clinical Dementia Rating (CDR), amyloid PET Standardized Uptake Volume Ratio (SUVr), amyloid burden on PET, and risks for adverse events. Results A total of four randomized controlled trials were included, involving 3,108 AD patients (1,695 lecanemab groups and 1,413 placebo groups) to synthesize evidence. Baseline characteristics of the two groups were similar in all outcomes except that ApoE 4 status and higher MMSE score were observed in the lecanemab group. It is reported that lecanemab was beneficial to stabilize or slow down the decrease in CDR-SB (WMD: −0.45; 95% CI: −0.64, −0.25; p < 0.00001), ADCOMS (WMD: −0.05; 95% CI: −0.07, −0.03; p < 0.00001), ADAS-cog (WMD: −1.11; 95% CI: −1.64, −0.57; p < 0.0001), amyloid PET SUVr (WMD: −0.15; 95% CI: −0.48, 0.19; p = 0.38), amyloid burden on PET (WMD:−35.44; 95% CI: −65.22,−5.67; p = 0.02), adverse events (subjects with any TEAE) (OR: 0.73; 95% CI: 0.25, 2.15; p = 0.57), ARIA-E (OR:8.95; 95% CI: 5.36, 14.95; p < 0.00001), and ARIA-H (OR:2.00; 95% CI: 1.53, 2.62; p < 0.00001) in early AD patients. Conclusion Our analysis found that lecanemab showed significant positive statistical efficacy with respect to cognition, function, and behavior in patients with early AD though the actual clinical significance is yet to be established Systematic review registration https://www.crd.york.ac.uk/PROSPERO/#recordDetails, identifier: CRD42023393393.